MANAGEMENT OF DISMENORE PAIN WITH EXERCISE STRETCH PAINT - Neni Nuraeni; Yuyun Solihatin; Rena I; Haifa N; Marisa L; Zakiyyah Zakiyyah (Universitas Padjadjaran, 2021)
Dysmenorhoe is a state of pain in the pelvis and the lower abdomen (suprapubic) that happened before or during menstruation. The symptoms of dysmenorrhoea are unpleasant, individually, and subjectively. It happens to teenagers more frequent, menstrual disturbances disorder often experienced, irregular menstrual among others have less and painful menstruation and have more often and affected to their learning process and absences at school because of the prolonged pain. Cat stretch exercise is one of a non-pharmacology kind. The purpose of the activities is to give training to students in reducing pain in SMUN of Tasikmalaya. Quantitative methods approach used one group pretest-posttest—the samples from 20 students with purposive sampling. Results obtained the average before intervention 2,10 and after 1,70 using the Numeric Rating Scale (NRS). T Independent result p 0,002 means cat stretch exercise can reduce dysmenorrhoea. Recommended for teenage girls to apply to do this exercise when experiencing dysmenorrhea.